1996
DOI: 10.1016/0895-7061(95)00392-4
|View full text |Cite
|
Sign up to set email alerts
|

Defective Endothelium-Dependent Relaxation in Fructose-Hypertensive Rats

Abstract: The present study examined the endothelium-dependent and -independent responses of isolated mesenteric arteries to acetylcholine and the endothelium-independent vasodilator sodium nitroprusside in mesenteric arteries from fructose-induced hypertensive rats. Fructose feeding resulted in hyperinsulinemia and elevated blood pressure when compared to controls (plasma insulin, 5.9 +/- 0.4 v control 3.6 +/- 0.4 ng/mL, P < .05; systolic blood pressure, 154 +/- 5 v control 127 +/- 7 mm Hg, P < .05). The maximum contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
40
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 39 publications
12
40
0
Order By: Relevance
“…Plasma insulin levels were markedly elevated in OZR and more moderately increased in FF-LZR compared with LZR. These data are consistent with the literature values (7,16,20) and indicate that fructose feeding induced a state of moderate insulin resistance, whereas obesity induces a more severe form. Plasma cholesterol and triglycerides were significantly elevated in both OZR and FF-LZR, consistent with insulin resistance.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Plasma insulin levels were markedly elevated in OZR and more moderately increased in FF-LZR compared with LZR. These data are consistent with the literature values (7,16,20) and indicate that fructose feeding induced a state of moderate insulin resistance, whereas obesity induces a more severe form. Plasma cholesterol and triglycerides were significantly elevated in both OZR and FF-LZR, consistent with insulin resistance.…”
Section: Resultssupporting
confidence: 82%
“…Insulin resistance is considered an emerging risk factor for vascular disease and has been documented to impair nitric oxide (NO)-dependent mesenteric vasodilation in animal models of insulin resistance (20,(22)(23)(24). Given that NO is a major contributor to absorptive functional hyperemia (1,9,12,17) and flow-mediated regulation (2,12,19), it raises the question of how the mesenteric circulation compensates for the impaired dilator response caused by insulin resistance against the elevated metabolic demands associated with increased ingestion of food in obese or hyperphagic individuals.…”
mentioning
confidence: 99%
“…Vagal dysfunction in fructose-fed female rats www.bjournal.com.br which was observed in the fructose-fed group of the present study, and hyperinsulinemia are the main causes for increased AP in the fructose model, and they are possibly responsible for sympathetic nervous system activation (6), impairment of endothelium-dependent relaxation (12,14) and dysfunction in angiotensin-renin system (5). This is the first study to evaluate cardiac autonomic control in female rats after high fructose consumption, using an invasive method.…”
mentioning
confidence: 93%
“…Thus the effect of insulin resistance on vascular signaling mechanisms is an area of increasing scrutiny. Insulin-resistant states and diabetes are associated with reduced endothelium-dependent relaxation, and this dysfunction of the endothelium is highly correlated with future cardiovascular events (1,14,34,49). In the obese Zucker rat (OZR), we previously showed that endothelium-dependent relaxation is impaired (14); however, the mechanisms underlying reduced synthesis or action of nitric oxide (NO) remain to be established.…”
mentioning
confidence: 99%